In-situ upgrading of heavy crude oils via solvent deasphalting using of nickel oxide nanoparticles as asphaltene co-precipitants. (1st April 2022) - Ovalles, Cesar; Rogel, Estrella; Vien, Janie; Morazan, Harris; Carbognani-Ortega, Lante; Lopez-Linares, Francisco; Rea, Thomas; Wei, Tao; Miao, Toni; Lee, Eddy; Moir, Michael E.
Highlights: NiO nanoparticles are effective asphaltene co-precipitants. Nanostructured NiO improves the upgraded crude oil properties. Formation of a carbon-containing layer encapsulates the nanosized NiO. Reaction involves Ni-O-carboxylate or phenolate on the NiO surface. Abstract: The use of NiO nanoparticles as asphaltene co-precipitant additives is studied to improve the upgraded oil's properties and potentially reduce the solvent-to-oil ratio for the in-situ upgrading of heavy oils via solvent deasphalting. Asphaltene content, solubility profile, and C7-deasphalting laboratory experiments were carried out to evaluate the efficiency of the nanomaterial. Results showed that nickel oxide nanoparticles increased the amount of asphaltenes in the 15–18% range with respect to the case without additive at the same solvent-to crude ratio. In the presence of the NiO nanoparticles, improvements on the upgraded crude oil properties were found with an average 17.1°API gravity (16% increase) and a viscosity of ∼2370 cSt (∼16% reduction) vs. the case without additive. These results demonstrate the usefulness of using nickel oxide nanoparticles to further enhance the upgraded crude oil properties for heavy oil upgrading via solvent deasphalting. Based on elemental analysis and spectroscopic techniques (scanning transmission electron microscopy with high angle annular dark field detection, energy dispersive X-ray analysis, Mid- and Far-FT-IR, and X-ray photoelectron spectroscopy), it was found that NiO nanoparticles acted as nucleation sites (agglomerants). A carbon-containing layer from the asphaltene fraction encapsulates the nickel oxide nanoparticles. A plausible mechanism for the interaction of the nanostructured NiO with the C7-asphaltenes was proposed that involves the formation of nanosized Ni-O-carboxylate or phenolate species on the surface of the nickel oxide nanoparticles.